The Possible Protective Effect of Simultaneous Administration of Alcoholic Ammi majus Seeds' Extract Against Gentamicininduced Nephrotoxicity in Rats - Shihab H. Muttlag; Ali A. Kasim; Ali R. Jassim (College of Pharmacy / Mustansiriyah University, 2012)
In gentamicin-induced nephrotoxicity, reactive oxygen species (ROS) is believed to play a pivotal role in cellular damage and necrosis via several complex mechanisms. Ammi majus L. (Apiaceae) is a rich source of many compounds which possess, among others, anti-oxidant activities. The aim of this study is to assess the possible protective effect of the alcoholic extract of Ammi majus seeds against gentamicin-induced nephrotoxicity. Eighteen rats were divided randomly into three groups: Group 1 (control) received a daily intraperitoneal (ip.) injection of 0.5 ml isotonic saline for six successive days. Group 2 received gentamicin dose of 100 mg kg−1day-1 (ip.), for six successive days. Group 3 received simultaneously the gentamicin dose (ip.) and aqueous solution of Ammi majusseeds' alcoholic extract (orally), at a dose of 128 mg kg-1 day-1 for six successive days. Serum urea, creatinin, tissue MDA and GSH concentrations were measured to assess the possible protective effects of Ammi majus. Serum creatinine and urea levels in Ammi majus treated group were lower than the group treated with gentamicin alone (P < 0.05). Simultaneous treatment with Ammi majus normalized the kidney tissue MDA content (P < 0.001) when compared to gentamicin-treated group. However, simultaneous treatment with Ammi majus provided a significant increase in kidney GSH levels (P < 0.05). In conclusion Ammi majus seeds' alcoholic extract has a protective effect against gentamicin-induced nephrotoxicity when given simultaneously. This protective effect may be mediated by the antioxidant activity of its active constituents. Further study is needed to assess the effect of treatment with Ammi majus extract before the gentamicin-induced nephrotoxicity